Large Angle Image Steering Using a Liquid Crystal Device. Issue 1 (June 2014) - Cheng, Hsien‐Hui; Bhowmik, Achintya; Bos, Philip J.
Abstract In this paper, we demonstrate a camera combined with a large angle non‐mechanical image steering device based on a Pancharatum phase grating. The image steering device can change the view direction of a camera to ±30° and ±10° and it is made by reactive mesogen polarization gratings (RMPGs) and liquid crystal polarization rotators (LCPRs). The image quality using this device is only slightly degraded at large angles.